The synergistic effect of digital economy and environmental governance on urban green development - Yuan, Rongze (Frontiers in Environmental Science, 2025)
IntroductionIn the context of escalating global climate change, cities play a crucial role in promoting green transformation, ecological construction, and achieving sustainable development goals. This study aims to explore the impact of the digital economy and environmental governance on urban green development.MethodsBased on data from 280 prefecture-level cities in China from 2007 to 2022, we construct a new indicator system to measure urban green development. Using a spatial error model, we analyze the relationship between the digital economy, environmental governance, and green urban innovation.ResultsThe findings indicate that the digital economy significantly promotes urban green development, with its impact influenced by geographical location and human capital. Environmental governance further enhances this positive effect, making the digital economy an essential driver of green urban innovation. Additionally, the implementation of China’s “Broadband China” policy has strengthened digital infrastructure, fostering green urban innovation and intercity cooperation.DiscussionThe study highlights the need for policymakers to consider geographical heterogeneity and human capital disparities when formulating digital and governance strategies. These insights provide valuable guidance for urban management and environmental protection efforts.